1998
DOI: 10.1093/bja/81.6.887
|View full text |Cite
|
Sign up to set email alerts
|

Continuous epidural infusion of ropivacaine for postoperative analgesia after major abdominal surgery: comparative study with i.v. PCA morphine

Abstract: We have compared the quality of three regimens of postoperative analgesia (continuous epidural administration of ropivacaine (Ropi. group), epidural ropivacaine and patient-controlled analgesia (PCA) with i.v. morphine (Ropi. + PCA group) and PCA morphine alone (PCA group)) during the first postoperative 24 h in a multicentre, randomized, prospective study. Postoperative analgesia was studied in 130 patients after major abdominal surgery performed under general anaesthesia. The ropivacaine groups received 20 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Nevertheless, the PCA delivery/demand ratio of morphine, an indicator of analgesia, was greater in the IT+PCA morphine group (Table III). 12,13 This prospective randomized study was not doubleblinded because of concerns with respiratory depression. Most reported cases of respiratory depression are due to the concomitant use of intrathecal morphine and parenteral morphine.…”
Section: Méthode : Soixante Patients Adultes Devant Subir Une Intervementioning
confidence: 99%
“…Nevertheless, the PCA delivery/demand ratio of morphine, an indicator of analgesia, was greater in the IT+PCA morphine group (Table III). 12,13 This prospective randomized study was not doubleblinded because of concerns with respiratory depression. Most reported cases of respiratory depression are due to the concomitant use of intrathecal morphine and parenteral morphine.…”
Section: Méthode : Soixante Patients Adultes Devant Subir Une Intervementioning
confidence: 99%
“…Most reports in literature have a protocol of thoracic epidural analgesia for perioperative pain management [2,3,6,8,10]. Prospective randomised control trials have found epidural analgesia superior to intravenous patient controlled analgesia (IV-PCA) in appropriate indications [11][12][13][14]. These patients may also require local anaesthetics with opioids via epidural for longer time than the conventional 48-72 h, with Schmidt et al [2] reporting median usage of 7 days continuous infusion.…”
Section: Pain Managementmentioning
confidence: 99%
“…Regional anaesthesia should be used whenever possible to decrease postoperative pain and the subsequent release of catecholamines, which can stimulate uterine contractility. 12 Continued epidural infusion of narcotics for up to 72 hours in an excellent way to minimize postoperative pain 13 .…”
Section: Usg Of Ovarian Cystmentioning
confidence: 99%
“…Cholecytectomy (45%) is the most common procedures performed during pregnancy followed by adnexal surgery (34%) and appendicectomy (15%). 13 The responsibility of caring for two patients during one operation and the concern over potential harm to the unborn fetus due to the pneumoperitoneum and / or instrumentation are factors that have played a role in the delay of adapting laparoscopic surgery safe to the pregnant patient. However, recent evidence suggests that not only is laparoscopic surgery safe in the pregnant patient in all three trimester, but it is also often preferable.…”
Section: Usg Of Ovarian Cystmentioning
confidence: 99%